2018
DOI: 10.14710/jbtr.v4i1.2546
|View full text |Cite
|
Sign up to set email alerts
|

Cytogenetic Analysis and Clinical Phenotype of Primary Amenorrhea in Indonesian Patients

Abstract: Background: Primary amenorrhea (PA) is a symptom that can be caused by different disorders such as gonadal, endocrinal, physiological and genetic disorders. Aim of study: This study provided the clinical and cytogenetic profiles of Indonesian primary amenorrhea patients and introduced clinical criteria of those patients with their  karyotype results using score system.  Methods: A retrospective descriptive study of 79 PA patients, whom referred to Cytogenetic and Molecular unit Center for Biomedical Research (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 12 publications
2
3
0
Order By: Relevance
“…Short stature and delayed puberty, and lack of incidence of secondary sexual characteristics were significant clinical symptoms amongst these patients. This result was in line with previous studies, which reported that TS is the most commonly observed CA in PA, and also strengthened the role of the sex chromosome in the reproduction of females [17,25,28]. In this study, out of 30 cases of SA, two (6.6%) revealed a variety of CA.…”
Section: Discussionsupporting
confidence: 92%
“…Short stature and delayed puberty, and lack of incidence of secondary sexual characteristics were significant clinical symptoms amongst these patients. This result was in line with previous studies, which reported that TS is the most commonly observed CA in PA, and also strengthened the role of the sex chromosome in the reproduction of females [17,25,28]. In this study, out of 30 cases of SA, two (6.6%) revealed a variety of CA.…”
Section: Discussionsupporting
confidence: 92%
“…Short stature and delayed puberty, and lack of incidence of secondary sexual characteristics were significant clinical symptoms amongst these patients. This result was in line with previous studies, which reported that TS is the most commonly observed CA in PA, and also strengthened the role of the sex chromosome in the reproduction of females ( Ali et al, 2018 ; Lekha et al, 2020 ; Soltani, Mirzaei & Ayatollahi, 2021 ).…”
Section: Discussionsupporting
confidence: 92%
“…16 Our study had a no patients with a typical Turner syndrome although mosaic variants were seen more commonly. Turners was attributed as the most common cause for PA. 17 Female patients can be offered advanced therapies like hormone therapy and marriage counseling. 16 Psychological support being the utmost important and central to genetic counseling.…”
Section: Discussionmentioning
confidence: 99%